Presence and function of SARS-CoV-2-specific T-cells in recovered patients and healthy volunteers - Le Bert, Nina (Henry Stewart Talks, 2020)
The need to characterise SARS-CoV-2-specific T-cells from recovered patients, Discovery of similar SARS-CoV-2-specific T-cells in healthy volunteers, Possible reasons for presence of SARS-2-specific T-cells in healthy volunteers, Differences in actions and behaviours of SARS-2-specific T-cells in patients versus volunteers, Role of SARS-2-specific T-cells in conferring pre-existing immunity to COVID-19 (i.e. asymptomatic infections), Possible implications of the presence of such cells on disease progression, Implications for vaccine development